Combination of fish oil with rubber seed oil to the growth performance of catfish (Clarias sp.). Issue 1 (March 2021) - Syamsunarno, M B; Tambunan, I D G; Munandar, A; Mustahal,; Putra, A N; Herjayanto, M
Abstract: The rubber seed oil contains essential fatty acids, which may be required by cultured freshwater fish. Therefore, the research aimed to determine a combination of fish oil and rubber seed oil for catfish's best growth performance (Clarias sp.). Isonitrogenous (33.23 ± 0.19%) and isoenergy (266.50 ± 0.09 DE kcal/100g) tested diets were used in the experiment. The fish oil was replaced by rubber seed oil at 0%, 15%, 25%, 35%, and 50%, respectively. Cyanide acid of rubber seed oil was reduced its content by stirring at 110 °C for 90 minutes to have as high as 0.47 ppm. Catfish fingerlings of 6.91 ± 0.04 g in individual weight were randomly distributed into 15 aquariums (60x40x40cm) each at a rate of 20 fingerlings and fed on the tested diet ad satiation for 40 days during the experimental period. The results showed that the increase in rubber seed oil to replace fish oil in the feed was not significantly different from the survival rate and nutrient retention in body catfish (P> 0.05). Furthermore, catfish were not poisoned by cyanide acid, indicated by catfish blood profile in the normal range at the end of rearing (P>0.05). The combination of fish oil and rubber seed oil by 50% gives optimal growth in catfish.